2000
DOI: 10.1159/000029126
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar II Disorder and Its Premorbid Personality

Abstract: This study psychopathologically analyzes and compares the premorbid personalities associated with bipolar II disorder and unipolar depression. Using Cloninger’s tridimensional personality theory, we evaluated 14 inpatients with bipolar II disorder and 14 inpatients with unipolar depression. The results indicate that the premorbid personality associated with bipolar II disorder is characterized as ‘the reward-dependent, passive-avoidant/dependent tendency of personality’ or ‘the dependent tendency of personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Other studies found more dependant, obsessive, histrionic traits, reward‐dependant, passive avoidant/dependant and similar personality profiles to unipolar disorder. More borderline features in bipolar II disorder is the single most consistent finding (7, 23, 46, 67–75). When one examines patients with borderline personality diagnoses, some 66% of borderlines have comorbid affective diagnoses (76), with bipolar II being particularly over‐represented (77).…”
Section: Clinical Featuresmentioning
confidence: 89%
“…Other studies found more dependant, obsessive, histrionic traits, reward‐dependant, passive avoidant/dependant and similar personality profiles to unipolar disorder. More borderline features in bipolar II disorder is the single most consistent finding (7, 23, 46, 67–75). When one examines patients with borderline personality diagnoses, some 66% of borderlines have comorbid affective diagnoses (76), with bipolar II being particularly over‐represented (77).…”
Section: Clinical Featuresmentioning
confidence: 89%
“…No study has been published using the newer TCI. Based on this model, some studies have tried to assess differences between the personality characteristics of the general population and patients with BD [11,21,22], BD type I and type II [14,29], as well as manic, euthymic and depressed states of BD [27]. Although the consistency of the results is poor and more studies are needed, we are going to assume for this research the following hypothesis: specific personality traits can serve as a phenotype marker for the genetic–neurochemical diathesis to BD [21].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of comorbid personality traits or disorders in patients with mood disorders has received considerable attention in recent years (1–5). Although the major focus of studies regarding comorbid personality disorders were initially on depression, studies searching for the relationship between bipolar disorder (BD) and personality disorder (PD) have been on the increase during the last decade (5–18). The presence of comorbid PD has been shown to be a prominent factor affecting symptom severity and course in BD patients.…”
Section: Introductionmentioning
confidence: 99%